Opening the Black Box of Intrahousehold Decision Making: Theory and Nonparametric Empirical Tests of General Collective Consumption Models - Cherchye, Laurens; De Rock, Bram; Vermeulen, Frederic (Journal of Political Economy, 2009)
We provide “revealed preference” tests of general collective consumption models that account for public consumption and externalities within the household. We further propose a novel approach to model special cases of this model, which imply alternative assumptions regarding the sharing rule. Our application uses the panel data from the Russia Longitudinal Monitoring Survey. We find that the general model, together with a large class of special cases, cannot be rejected. By contrast, we do reject the standard unitary model. Since our tests are entirely nonparametric, this provides strong evidence in favor of models focusing on intrahousehold decision making.